Pengembangan Media Pembelajaran Matematika Berbasis YouTube Pada Materi Perbandingan Trigonometri - Yudela, Shintia; Putra, Aan; Laswadi, Laswadi (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2020)
The use of technology in education is becoming increasingly common. So that in its development, educators must be able to take advantage of information and communication technology in the learning process. Efforts to use it are to increase the attractiveness of a learning process, one of which is by using the help of learning media. Because of this, this study aims to produce YouTube-based learning media on trigonometric comparison material, find out expert opinions and student responses to YouTube-based mathematics learning media on trigonometric comparison material from an angle. This research is a research development or Research and Development (R & D) using the Sugiyono procedure. This research was conducted at MAS Nurul Haq Semurup with the research subjects being students of class X. Data collection was carried out using interviews and questionnaires. The instrument used was a questionnaire using a Likert scale. Based on the results of the validation carried out by material experts and media experts, the percentage results were respectively 71% and 77% with valid criteria. Then the learning media was tested through 2 stages, namely small group trials and field trials. The average results obtained were 87.22% for small group trials and 88.16% for field trials with very practical interpretation criteria, so it can be concluded that YouTube-based mathematics learning media on trigonometric comparison material from an angle is valid and practical to use in learning. Overall the results of the study indicate that the learning media developed are suitable for use by students.